KEBIJAKAN PEMBERDAYAAN MASYARAKAT DI DESA LANTA KECAMATAN LAMBU KABUPATEN BIMA - wawan mulyawan (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
ABSTRACT This study aims to: 1) To find out the strategy of community empowerment in development activities in Lanta Village, Lambu District, Bima Regency; 2) To find out the stages of community empowerment in development activities in Lanta Village, Lambu District, Bima Regency; 3) To find out the follow-up of community empowerment in development activities in Lanta Village, Lambu District, Bima Regency. In discussing this research, researchers used descriptive qualitative research, with data collection techniques used, namely interviews, observation, and documentation. Determination of key informants using purposive sampling technique with the number of key informants as many as 5 (five) people. The results showed that community empowerment strategies in development activities in Lanta Village, Lambu District, activities to strengthen the knowledge that the community has in community empowerment and plan development activities that are physical and non-physical in Lanta Village, this can be seen from the level of enthusiasm, mutual cooperation and togetherness of the community in the implementation of development; Stages of community empowerment in development activities in Lanta Village, Lambu District, Bima Regency are very good, this can be seen from the level of togetherness, cooperation and activeness as well as very good community participation because the Village Government is always informed before carrying out activities, and; Follow-up of community empowerment in development activities in Lanta Village. Keywords: Policy, Empowerment, and Community